Obese mice induced by high-fat diet have differential expression of circular RNAs involved in endoplasmic reticulum stress and neuronal synaptic plasticity of hippocampus leading to obesity-associated cognitive impairment - Niu, Yan; Chang, Pan; Liu, Tian; Shen, Xi; Zhao, Hui; Zhang, Mingxia; Lei, Shengping; Chen, Baoying; Yu, Jun (Frontiers in Molecular Neuroscience, 2022)
Obesity induced by high-fat diet (HFD) is an important cause of impaired memory and cognitive function, but the underlying mechanisms are not clear. In the present study, we analyzed the levels of circRNAs in hippocampus of C57BL/6J mice and valuated the ability of memory and cognition of C57BL/6J mice with HFD using morris water maze and Y-maze approaches to explore the potential mechanisms linking circRNAs in obesity-associated cognitive impairment. Learning performance showed that HFD-induced obesity mice have impaired memory andcognition. The array-star analysis of hippocampus displayed that HFD-induced obesity leads to the differential expression of circRNAs (DE-circRNAs) in mice. In total, 46 circular RNAs with elevated expression and 10 with decreased expression were identified. Among them, mmu_circRNA_004797 was identified and significantly downregulated and expression of mmu_circRNA_21040 significantly upregulated in HFD-fed mice, compared with control mice by PCR test. Bioinformatics analysis also showed the upregulated circRNAs were related to the neuronal function and behavior, material transport process and downregulated circRNAs participated in process of cell response to external stimuli such as cellular response to nutrient levels. Furthermore, the KEGG pathway analysis showed up-regulated circRNAs are mainly involved in Axon guidance, Calcium signaling pathway and ErbB signaling pathway. Only a single significant pathway,‘Protein processing in endoplasmic reticulum’was observed in down-regulated circRNAs. Finally, we examined the deficits of hippocampal synaptic plasticity and detected the expression of ER stress related protein. The result showed that ER stress was activated in hippocampus and hippocampal synaptic plasticity deficits were displayed. Our results demonstrated that circRNA were most likely implicated in the predisposition to obesity associated cognitive impairment.